Studies of radon-exposed miner cohorts using a biologically based model: comparison of current Czech and French data with historic data from China and Colorado - Heidenreich, W F; Tomásek, L; Rogel, A; Laurier, D; Tirmarche, M (Radiation and environmental biophysics, 2004)
The biologically based two-stage clonal expansion (TSCE) model is used to analyze lung cancer in several miners studies, two new ones (Czech, French) and two historic ones (Chinese, Colorado). In all cases, the model assumptions are identical. An action of radiation on initiation, promotion, and transformation is allowed. While all four studies indicate a highly significant action of radiation on promotion, the action on initiation is not significant in the French cohort, and barely significant in the Colorado miners cohort. No action on transformation is found in the Colorado miners, while the other data sets indicate a borderline significance. The model can describe all the data sets adequately, with different model parameters. The observed patterns in exposure, time since beginning of exposure, birth year, age and calendar year are reproduced well. The doubling exposure rate for initiation is about 3.5 WLM/year in the new data sets, while it is higher in the historic data sets. For transformation the doubling rate is about 20 WLM/year for the new data sets, while again the historic data give higher estimates. The action of radiation on promotion is quite different in the four data sets. These differences also induce different risk estimates at low exposures. The larger power of the new studies at these low exposures, compared to the historic data requires less extrapolation when the risk at very low exposures is estimated.
Keywords: Čína; proporcionální rizikové modely; Proportional Hazards Models; dávka záření; Dose-Response Relationship, Radiation; Relative Biological Effectiveness; algoritmy; Algorithms; Computer Simulation; Age Distribution; Incidence; Česká republika; počítačová simulace; Cohort Studies; Risk Assessment; Body Burden; vztah dávky záření a odpovědi; nádory plic; Neoplasms, Radiation-Induced; incidence; China; radon; Czech Republic; kohortové studie; obsah radioaktivních látek v organizmu; Radiation Monitoring; Mining; monitorování radiace; Models, Biological; hodnocení rizik; Colorado; Humans; věkové rozložení; Radiation Dosage; Radon; hornictví; Francie; relativní biologická účinnost; biologické modely; rizikové faktory; France; nádory vyvolané zářením; Risk Factors; Lung Neoplasms; lidé